Veronica ruiz breaks the bank ebook A short story. - Cosimano, Elle (Finlay Donovan, 2023)
From New York Times bestselling author Elle Cosimano, comes Veronica Ruiz Breaks the Bank —a hilarious short story diving into Finlay Donovan's partner-in-crime Vero's past. Anyone can spot a window of opportunity, but not everyone can manage to fall straight through one. Veronica Ruiz is on the run for the first time in her life — though certainly not the last. After being falsely accused of stealing money from her college sorority, she packs up and heads to her cousin Ramón's apartment, planning to change her name and start over, away from backstabbing girls and university drama (and far, far away from her arrest warrant in Maryland). At the local bank on the first morning of her new life, it occurs to Vero that she'd be a better bank teller than most of the current employees; she may not have much money, but what little she does have, she knows how to manage. Unfortunately, the only available position is a cleaning job and so, desperate for a fresh start, she takes the bank manager's offer. But nothing in Vero's world has ever been simple so of course, shortly after she begins work, she overhears a conversation between her new boss and a security guard: someone who works there has been stealing. Seeing a window of opportunity, Vero sets out to find the identity of the thief, present the evidence, and then push for the perfect job. All of which would be easier if her irresistibly infuriating childhood crush Javi wasn't living in the same damn town. Offering the insight that readers have been craving into fan-favorite Vero's past and a closer look at the moment Finlay and Vero first meet, Veronica Ruiz Breaks the Bank is a can't-miss addition to the Finlay Donovan series.